2018
DOI: 10.1093/annonc/mdy089
|View full text |Cite
|
Sign up to set email alerts
|

Combined immunotherapy encompassing intratumoral poly-ICLC, dendritic-cell vaccination and radiotherapy in advanced cancer patients

Abstract: This radio-immunotherapy combination strategy, aimed at resembling viral infection in tumor tissue in combination with a dendritic-cell vaccine and SABR, is safe and shows immune-associated activity and signs of preliminary clinical efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 34 publications
1
91
0
2
Order By: Relevance
“…Published previous experience using TGFb blockade with mAbs in monotherapy showed improved local tumor control of radiotherapy without abscopal effects (33). We have observed that TGFb blockade achieves abscopal effects beyond the previously reported spectacular effects reached by unilateral radiotherapy plus anti-PD-1 plus anti-CD137 mAbs in combination (3,18). In our hands, the quadruple combination approach achieves abscopal effects against large and well-established transplanted tumors.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Published previous experience using TGFb blockade with mAbs in monotherapy showed improved local tumor control of radiotherapy without abscopal effects (33). We have observed that TGFb blockade achieves abscopal effects beyond the previously reported spectacular effects reached by unilateral radiotherapy plus anti-PD-1 plus anti-CD137 mAbs in combination (3,18). In our hands, the quadruple combination approach achieves abscopal effects against large and well-established transplanted tumors.…”
Section: Discussionsupporting
confidence: 52%
“…The role of radiotherapy as a means to augment response to immunotherapy has been explored in preclinical models (1,2) and is currently being studied in multiple clinical trials (3)(4)(5)(6)(7). The most interesting experiments are those in which radiation elicits efficacy outside the irradiation fields, the so-called abscopal effects of radiotherapy (1,8).…”
Section: Introductionmentioning
confidence: 99%
“…Different TLR agonists have been tested in experimental mouse tumors models [22][23][24][25] and are being investigated in early clinical trials to assess their safety and efficacy in cancer patients, most frequently in combination with conventional or target therapies [26][27][28]. Here, we have studied the TLR7 agonist Imiquimod (IMQ), one of the few approved by FDA for the treatment of nonmelanoma skin cancers [26,29], and the TLR3 agonist Poly(I:C), a dsRNA analog under study in the clinic as adjuvant in antitumor vaccines [27,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…This case demonstrates the role of radiations in ensuring the release of disruptions to the blood-brain barrier and tumorassociated antigens [12]. AbEs are mainly sporadic events of tumors that begin to grow following RT treatments as observed through irradiated sites from a distance [13]. Mechanisms often have several origins, including infection by inflammatory agents such as cytokines, the distance effects, and the secondary immunity to devices [14].…”
Section: Abscopal Effects -Current and Future Practicesmentioning
confidence: 91%